Parents' Experiences of Having a Young Child With Acute Lymphoblastic Leukemia in China. (March 2021) - Liu, Qian; Petrini, Marcia A.; Luo, Dan; Yang, Bing Xiang; Yang, Jiong; Haase, Joan E.
Background: Understanding parents' experiences is a prerequisite to developing interventions that are sensitive to needs of children and families. In China, little is known about parental experiences of having a young child with acute lymphoblastic leukemia (ALL). This phenomenological study aimed to describe parental experiences of having a young child with ALL in China. Method: Ten parents, recruited in central China using purposive sampling, participated in face-to-face, in-depth interviews using Haase's adaptation of Colaizzi's phenomenological method. Results: Five theme categories were identified: (a) The Cancer Diagnosis as a Terrible Disaster—The Sky is Falling, (b) Fighting the Beast, (c) Putting on a Happy Face and Other Coping Strategies, (d) Diagnosis Disclosure: If We Tell and How to Tell, and (e) Hope-Filled Expectations: Returning to Normal Life. Conclusion: Parents put their child's health as their top priority. They strive to manage uncertainty about prognosis and cope with enormous pressures caused by children's suffering, financial burden, and stigma. Parents also express their resilience and hope throughout their child's cancer journey. Support services to strengthen specific families' protective factors (i.e., family/community support, hope, and positive coping) are needed to foster resilience and quality of life. Health care professionals should systematically assess parents' needs, provide validated education materials, and implement tailored interventions across the cancer continuum. Public education and advocacy about cancer is also necessary to decrease cancer-related stigma, and provide financial aid and health care resources in pediatric oncology.